2002
DOI: 10.1038/sj.bjc.6600654
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of coregulator and oestrogen receptor isoform expression to de novo tamoxifen resistance in human breast cancer

Abstract: This study addresses the hypothesis that altered expression of oestrogen receptor-beta and/or altered relative expression of coactivators and corepressors of oestrogen receptors are associated with and may be mechanisms of de novo tamoxifen resistance in oestrogen receptor positive breast cancer. All cases were oestrogen receptor +, node negative, primary breast tumours from patients who later had no disease progression (tamoxifen sensitive) or whose disease progressed while on tamoxifen (tamoxifen resistant).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 30 publications
7
49
1
3
Order By: Relevance
“…Although there is a general consensus that the presence of ERa predicts response to tamoxifen (ERa-negative tumours rarely respond), the literature relating to ERb and response to tamoxifen is confusing and conflicting. In part, this is because studies have been performed in two different settings, giving tamoxifen either as an adjuvant to surgery and measuring recurrence rates/times (Murphy et al, 2002;Davies et al, 2004;Esslimani-Sahla et al, 2004;Hopp et al, 2004;O'Neill et al, 2004) or as neoadjuvant treatment and monitoring changes in the size of the primary tumours. In general, the latter studies are more applicable to tumour sensitivity to therapy, as recurrence in the adjuvant setting is determined not only by response to systemic treatment but also by the extent of micrometastatic disease and inherent aggressiveness of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a general consensus that the presence of ERa predicts response to tamoxifen (ERa-negative tumours rarely respond), the literature relating to ERb and response to tamoxifen is confusing and conflicting. In part, this is because studies have been performed in two different settings, giving tamoxifen either as an adjuvant to surgery and measuring recurrence rates/times (Murphy et al, 2002;Davies et al, 2004;Esslimani-Sahla et al, 2004;Hopp et al, 2004;O'Neill et al, 2004) or as neoadjuvant treatment and monitoring changes in the size of the primary tumours. In general, the latter studies are more applicable to tumour sensitivity to therapy, as recurrence in the adjuvant setting is determined not only by response to systemic treatment but also by the extent of micrometastatic disease and inherent aggressiveness of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated with chemotherapy as well as TAM, ERβ expression also significantly correlates with increased OS [97,105] and DFS [94,97,104,105]. Higher ERβ expression is observed more frequently in TAM-sensitive breast tumors than in TAM-resistant tumors [113], and lower ERβ is associated with TAM resistance [107,113,114]. One study analyzing 138 postmenopausal patients with invasive cancer observed a trend toward worse outcome in ERβ+ patients treated with TAM, although it was not statistically significant and only seventeen ERβ− tumors were used in this comparison.…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 96%
“…Iwase et al have reported that patients with ERβ+ tumors tend to have a better response to endocrine therapy than those with ERβ− tumors [112]. In breast cancer patients treated with adjuvant TAM, high ERβ expression significantly correlates with increased overall [86,107] and disease-free survival [107], no disease progression [113], or no relapse within five years [93,114]. In patients treated with chemotherapy as well as TAM, ERβ expression also significantly correlates with increased OS [97,105] and DFS [94,97,104,105].…”
Section: Clinical Correlations Between Erβ Expression and Response Tomentioning
confidence: 99%
See 1 more Smart Citation
“…There is little consensus however as to the direction of these changes. Steroid receptor coactivator 1 and AIB1 mRNA levels have been associated with tumour progression; however, studies investigating coactivator RNA expression and resistance to ER modulators failed to demonstrate a significant association (Murphy et al, 2000(Murphy et al, , 2002. Recent studies have reported positive associations between AIB1 protein expression, high tumour grade and coexpression with the coactivators p300/ CBP (Hudelist et al, 2003).…”
mentioning
confidence: 99%